DIGITAL TECHNOLOGIES IN TEACHING AND TEACHER EDUCATION ACCORDING TO THE VIEW OF MATHEMATICS UNDERGRADUATE STUDENTS - Idem, Rita de Cassia [UNESP]; Rodrigues da Silva, Ricardo Scucuglia [UNESP] (Centro Univ Nove Julho, 2021)
This qualitative study aimed to present and discuss the views of future teachers in relation to the integration of digital technologies in the teaching of Mathematics and in the teacher education. Four students participated in the research at different levels of the Mathematics course at a public university in Sao Paulo. The data were produced by audio recording in the context of a university extension course, which sets up the research scenario. This course was aimed at teachers and future mathematics teachers and addressed the possibilities of GeoGebra for teaching and learning of Plane and Spatial Geometries, in addition to promoting discussions on the integration of digital technologies in teaching. This present study focuses on a discussion that took place at one of the meetings of the course. This discussion was considered a collective interview and was analyzed in the light of qualitative processes. The results, which are presented through categories and subcategories, show that the students consider that digital technologies are important both in the learning of mathematical content and in the education of future teachers, but they evaluate that this theme has been neglected in their own education, and in the teaching Mathematics in Basic Education.
Keywords: Mathematics education; Prospective teacher education; Digital technologies